2014
DOI: 10.1093/humrep/deu261
|View full text |Cite
|
Sign up to set email alerts
|

ESX1 mRNA expression in seminal fluid is an indicator of residual spermatogenesis in non-obstructive azoospermic men

Abstract: This work was supported by the Fondazione IRCCS Ca' Granda, Ospedale Maggiore Policlinico: Ricerca Corrente [grant number RC2014/519-02] to M.M. and from ASM onlus 2010-2011 to M.M. The authors declare that they have no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…The prediction of sperm retrieval by TEX101 was comparable to other biomarkers that predict sperm retrieval, including seminal protein LGALS3BP (AUC = 0.76; 100% sensitivity at 45% specificity) [39], seminal leptin (AUC = 0.59; 43% sensitivity at 75% specificity) [40], seminal ESX1 mRNA (84% sensitivity at 28% specificity) [41], and blood serum FSH protein (AUC = 0.62; 71% sensitivity at 68% specificity) [40]. Better biomarkers to predict sperm retrieval in NOA patients are still required.…”
Section: Discussionmentioning
confidence: 80%
“…The prediction of sperm retrieval by TEX101 was comparable to other biomarkers that predict sperm retrieval, including seminal protein LGALS3BP (AUC = 0.76; 100% sensitivity at 45% specificity) [39], seminal leptin (AUC = 0.59; 43% sensitivity at 75% specificity) [40], seminal ESX1 mRNA (84% sensitivity at 28% specificity) [41], and blood serum FSH protein (AUC = 0.62; 71% sensitivity at 68% specificity) [40]. Better biomarkers to predict sperm retrieval in NOA patients are still required.…”
Section: Discussionmentioning
confidence: 80%
“…Different studies recently identified seminal proteins including ECM1, TEX101 (Drabovich et al, 2013;Rolland et al, 2012) or trace RNA including DDX4, SEMG1, TGM4 and ESXI (H. Li, Wu, Gu, & Xiong, 2012;Pansa et al, 2014). We also studied the relative expression of ESX1, ZMYND15, SPEM1, TNP1 and PRM1 mRNA in testicular biopsies of individuals with NOA, and we concluded the post-meiotic markers were more suitable for prediction of successful sperm retrieval following mTESE (Hashemi et al, 2018a(Hashemi et al, , 2018b.…”
Section: Discussionmentioning
confidence: 81%
“…Some molecular markers have previously been proposed; for example, ESX1 was identified in 95.4% of studied cases and showed a specificity of 74% and sensitivity of 80% for predicting residual spermatogenesis [29]. In a study by Ando et al [22], the level of VASA transcription was evaluated using RT-qPCR in 52 samples from men with NOA, and it was demonstrated to be a predictive factor for sperm recovery, with 86.2% specificity and 87.0% sensitivity.…”
Section: Discussionmentioning
confidence: 99%